2019
DOI: 10.1097/md.0000000000015682
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of drug-eluting bead transarterial chemoembolization (DEB-TACE) combined with radiofrequency ablation versus DEB-TACE alone in Chinese hepatocellular carcinoma patients

Abstract: To compare the efficacy of drug-eluting bead transarterial chemoembolization combined with radiofrequency ablation (DEB-TACE+RFA) versus DEB-TACE alone in Chinese hepatocellular carcinoma (HCC) patients. The 28 patients receiving DEB-TACE+RFA and 74 HCC patients receiving DEB-TACE were recruited in this study. Treatment responses, progression-free survival (PFS), and overall survival (OS) were evaluated. One to 3 months after treatments, the proportion of patients achieving complete respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(2) DEBs are able to release antitumor medicine continuously and slowly in tumor tissues, which can significantly increase the drug concentration in tumor tissues and control recurrence. (3) Microspheres firmly combined with antitumor drugs can dramatically decrease the amount of medicine released into the body circulation, thus decreasing the toxic side effects of drugs [ 12 , 13 ]. Currently, DEB-TACE is widely applied in primary liver cancer with satisfactory results [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) DEBs are able to release antitumor medicine continuously and slowly in tumor tissues, which can significantly increase the drug concentration in tumor tissues and control recurrence. (3) Microspheres firmly combined with antitumor drugs can dramatically decrease the amount of medicine released into the body circulation, thus decreasing the toxic side effects of drugs [ 12 , 13 ]. Currently, DEB-TACE is widely applied in primary liver cancer with satisfactory results [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these results were comparable to those reported in other literature on the treatment of unresectable HCC with DEB-TACE. 11 , 12 However, they were significantly better than previously reported survival of c-TACE in the treatment of advanced HCC. 13 , 14 The primary objective of this study was to identify factors that affect the prognosis of DEB-TACE in the treatment of unresectable HCC and to establish a simple, practical, and reliable prognostic scoring system to predict the efficacy and survival benefit of DEB-TACE in HCC patients.…”
Section: Discussionmentioning
confidence: 76%
“…Ahmed et al[ 43 ] found that RFA can increase the permeability of capillaries by dilating the nutritional blood vessels of the tumor, which is conducive to the residual chemotherapy drugs acting on tumor tissue. Zhu et al[ 44 ] found that the combined application of DEB-TACE and RFA improved the efficacy and survival time. However, combined treatment will increase the cost and prolong the hospital stay.…”
Section: Discussionmentioning
confidence: 99%